Evaluation of biochemical parameter in polycystic ovarian disease patients attending tertiary care hospital - Saha, Aditi; Gupta, Anirban Das (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: PCOS might be a complex multigenic disorder with strong epigenetic and environmental influences, such as diet and other lifestyle factors. It is associated with abdominal adiposity, insulin resistance, obesity, metabolic disorders and cardiovascular risk factors. Based on literature search and non-uniformity in the finding of various author present study has been designed to evaluate the biochemical parameter in polycystic ovarian disease patients attending tertiary care hospital. Methods: The study population include 50 untreated patients diagnosed to be polycystic ovarian disease. Parameters like age, BMI (body mass index), fasting plasma glucose, lipid profile overnight fasting plasma insulin, dehydroepiandrosterne sulphate, (µg/dl) (DHEAS), LH, FSH, LH/FSH ratio, HOMA IR (homeostasis model assessment of insulin resistance) and quantitative insulin sensitivity check index (QUICKI) and fasting serum plasma glucose to insulin ratio was measured in both group of patients. Results: The mean value of glucose insulin ratio was 4.88±1.911 in PCOD group and 8.74±4.61 in control group, the p value was 0.004909. The mean of LH/FSH ratio was 1.93±0.42 in PCOD group and 1.03±0.199 in control group. The p value was <0.05. The mean of HOMA IR was 7.87±0.87 in PCOD group and 2.036±0.26 in control group, with p value 0.00001. Conclusions: From present study we can conclude that the mean age was 22.05±4.649 years and the mean BMI was 27.32±6. Hyperglycemia and dyslipidemia were common in PCOD patients. The mean of HOMA IR was significantly higher and the mean value of QUICKI was significantly lower in PCOD group.